Profile of alopecia areata in patients attending dermatology out patient department in a tertiary care hospital in Gangtok, Sikkim - Gupta, Nisha; Sharma, Rekha; Sharma, Rukma L. (International Journal of Research in Dermatology, 2021)
Background: Alopecia areata is a condition that is characterized by a well-defined round or oval patches of non-scaring hair loss in scalp or any hairy area of the body. Alopecia areata has become a major health problem faced by people all over the world. This research was done to ascertain the prevalence of alopecia areata in different age group and to study its association with autoimmune diseases and systemic illnesses. Methods: The present hospital based descriptive study includes 52 alopecia areata patients attending dermatology out-patient department. Results: It was seen that the disease can occur at any age group mostly affecting those between 21-40 years. The age of presentation varied from 14 to 48 years with male preponderance. It was found that arthritis was associated in 30.7%, ANA was positive in 7.7% and 12% had hypothyroidism. Eosinophilia was found in 34.6% and 7.7% had asthma among then. Conclusions: Our study shows that it could be associated with autoimmunity, thyroid abnormality, atopy and inflammation.